Pengelompokan Provinsi Di Indonesia Berdasarkan Determinan Kesehatan Balita Dengan Menggunakan Analisis Cluster Tahun 2018 - Septia Nur Azizah; Erni Tri Astuti (Seminar Nasional Official Statistics, 2022)
Toddlers are one of the groups that are vulnerable and sensitive to nutritional and health problems. Indicators of mortality, nutritional status, and morbidity rates can be used to measure the health of status of toddlers. Based on the 2012 IDHS, 40 toddlers died before reaching the age of 5 years and according to Riskesdas 2018, 30 to 31 toddlers were stunted. Nationally, the mortality rate of toddlers range in Indonesia reaches 87 people and the the stunting prevalence range reaches 25 percent, which shows the disparity in the health of toddlers between regions and shows that the health of toddlers in Indonesia tends to be low. So, it is necessary to group provinces to see the characteristics of each province and identify priority areas. The analysis method applies k-means clusters with a coverage of 34 province in Indonesia. The result of the grouping formed 3 clusters, namely cluster 1 is a provinces with a moderate degree of toddler health, cluster 2 is a provinces with a good degree of toddler health and cluster 3 is a provinces with a poor degree of health of toddlers.